Biomarkers in the diagnosis of pleural diseases: a 2018 update. (October 2018) - Porcel, José M.
The use of biomarkers on pleural fluid (PF) specimens may assist the decision-making process and enhance clinical diagnostic pathways. Three paradigmatic examples are heart failure, tuberculosis and, particularly, malignancy. An elevated PF concentration of the amino-terminal fragment of probrain natriuretic peptide (>1500 pg/ml) is a hallmark of acute decompensated heart failure. Adenosine deaminase, interferon-γ and interleukin-27 are three valuable biomarkers for diagnosing tuberculous pleurisy, yet only the first has been firmly established in clinical practice. Diagnostic PF biomarkers for malignancy can be classified as soluble-protein based, immunocytochemical and nucleic-acid based. Soluble markers (e.g. carcinoembryonic antigen (CEA), carbohydrate antigen 15–3, mesothelin) are only indicative of cancer, but not confirmatory. Immunocytochemical studies on PF cell blocks allow: (a) to distinguish mesothelioma from reactive mesothelial proliferations (e.g. loss of BAP1 nuclear expression, complemented by the demonstration of p16 deletion using fluorescence in situ hybridization, indicate mesothelioma); (b) to separate mesothelioma from adenocarcinoma (e.g. calretinin, CK 5/6, WT-1 and D2-40 are markers of mesothelioma, whereas CEA, EPCAM, TTF-1, napsin A, and claudin 4 are markers of carcinoma); and (c) to reveal tumor origin in pleural metastases of an unknown primary site (e.g. TTF-1 and napsin A for lung adenocarcinoma, p40 for squamous lung cancer, GATA3 and mammaglobin for breast cancer, or synaptophysin and chromogranin A for neuroendocrine tumors). Finally, PF may provide an adequate sample for analysis of molecular markers to guide patients with non-small cell lung cancer to appropriate targeted therapies. Molecular testing must include, at least, mutations of epidermal growth-factor receptor and BRAF V600E, translocations of rat osteosarcoma and anaplastic lymphoma kinase, and expression of programmed death ligand 1.